A practical, chemoselective approach to O-methylation of carboxylic acids with dimethyl malonate. Issue 48 (2nd December 2015) - Mao, Jincheng; Liu, Defu; Li, Yongming; Zhao, Jinzhou; Rong, Guangwei; Yan, Hong; Zhang, Guoqi
Abstract: A practical and chemoselective method is described for the O-methylation of carboxylic acids. Dimethyl malonate, a low toxic and commercially available compound was found to be an effective methylating reagent for a variety of carboxylic acids affording methyl ester products in good to high yields and with excellent chemoselectivity, without the use of strong bases as additives. A mechanism involving the utilization of potassium bromide is tentatively proposed. Graphical abstract: